2017
DOI: 10.1038/s41598-017-11640-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide functional analysis reveals that autophagy is necessary for growth, sporulation, deoxynivalenol production and virulence in Fusarium graminearum

Abstract: Autophagy is a conserved cellular recycling and trafficking pathway in eukaryotic cells and has been reported to be important in the virulence of a number of microbial pathogens. Here, we report genome-wide identification and characterization of autophagy-related genes (ATGs) in the wheat pathogenic fungus Fusarium graminearum. We identified twenty-eight genes associated with the regulation and operation of autophagy in F. graminearum. Using targeted gene deletion, we generated a set of 28 isogenic mutants. Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 66 publications
(72 reference statements)
7
65
0
1
Order By: Relevance
“…Autophagy is known to be important for sexual reproduction in fungi (Wang et al, 2011;Voigt and Poggeler, 2013;Lv et al, 2017). Recently, it has been reported that A-to-I RNA editing occurs specifically during sexual reproduction in F. graminearum, N. crassa and other filamentous ascomycetes (Liu et al, , 2017.…”
Section: Ancient Duplication and Divergence Of Atg8 In Dermatophytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagy is known to be important for sexual reproduction in fungi (Wang et al, 2011;Voigt and Poggeler, 2013;Lv et al, 2017). Recently, it has been reported that A-to-I RNA editing occurs specifically during sexual reproduction in F. graminearum, N. crassa and other filamentous ascomycetes (Liu et al, , 2017.…”
Section: Ancient Duplication and Divergence Of Atg8 In Dermatophytesmentioning
confidence: 99%
“…In plants, autophagy is important for seedling establishment, plant development, senescence, stress resistance, metabolism and reproduction (Liu et al, 2005;Bassham et al, 2006;Avila-Ospina et al, 2014;Michaeli et al, 2016). In fungi, autophagy affects growth, morphology, development, lipid turnover and sexual reproduction (Kershaw and Talbot, 2009;Pollack et al, 2009;Nguyen et al, 2011;Josefsen et al, 2012;Liu et al, 2012;Duan et al, 2013;Voigt and Poggeler, 2013;Lv et al, 2017). In fungal pathogens, autophagy is also known to be important for plant or animal infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second category consists of Atg6, Vps38, Vps34 and Vps15, which are mainly involved in the endocytic pathway. It was recently reported that in nematodes, Atg6 regulates the processes of endocytosis Fusarium graminearum Reduced Reduced [27] and autophagy through the competitive binding of Vps38 and Atg14, and crosstalk exists between these two pathways, i.e., the autophagy pathway is promoted if the endocytic pathway is inhibited. This phenomenon has also been observed in fungi [19].…”
Section: Biological Process and Function Of Autophagymentioning
confidence: 99%
“…This suggests that the shift of infection mechanisms may be regulated by nutrient deprivation during the biotrophic phase (Brown et al 2017). Indeed, autophagy mechanisms used to maintain homeostasis in fungal cells and recycle nutrients were shown to be necessary for growth and pathogenicity (Lv et al 2017). Furthermore, Brown et al (2017) found that the expression of several effector genes were upregulated during infection and interestingly, this secreted protein cocktail appears to be specific for each phase and their location in the genome aligns with high recombination regions.…”
Section: Host-pathogen Interactionmentioning
confidence: 99%